Pickering emulsions stabilized by zein-proanthocyanidins-pectin ternary composites (ZPAAPs): Construction and delivery studies. (15th March 2023) - Li, Wenjing; Huang, Dongjie; Song, Weixuan; Ouyang, Fangxin; Li, Wenxuan; Song, Ye; Li, Feng; Jiang, Yang; Huang, Qingrong; Li, Dapeng
Highlights: Composite particles (ZPAAPs) exhibit near neutral-wettability. The emulsion is pink due to the presence of proanthocyanidins. ZPAAPs stabilized Pickering emulsion is an effective curcumin delivery system. Abstract: Proanthocyanidins (Pas) are widely used in the preparation of functional foods due to their diverse biological activities. Taking advantage of the effect of Pas on the stability of Pickering emulsions, this study constructed the zein-proanthocyanidins-pectin ternary composites (ZPAAPs) as stabilizer to establish Pickering emulsions with potential delivery capacity. The appearance of the emulsion was pink which could be found in visual observation. The emulsion was stable during long-term storage in the range of 0.1 ∼ 0.7 oil phase. CLSM showed that the oil droplets were coated with covering layer formed by ZPAAPs, which effectively prevented droplets congregating. The rheological results indicated that ZPAAPEs had elastic gel-like structure. In addition, ZPAAPEs still contained 54.4 % curcumin after storage for 15 d. And the bioavailability of curcumin was increased to 39.7 % ± 0.3. These studies may contribute to the controllable fabrication of Pickering emulsions for nutrient delivery in the food and pharmaceutical fields.